Uji Mekanik Film Chitosan-PVA-Antosianin Beras Merah - Fita Widiyatun (Universitas Indraprasta PGRI Jakarta, 2018)
Researches on film-making, especially on edible films, degradable films, etc. have been often conducted in Indonesia. The research is part of research on the production of films to be used as milk drinks indicators. The aim of the research is to produce a film from Chitosan, PVA (Polyvinyl Alcohol) and Anthocyanin from red rice. The film will be then tested mechanically. Mechanical tests used include tensile strength and elongation testing. The method applied to measure tensile strength and elongation is ASTM D882. The test results show the tensile strength value of 109.62 kgf / cm2 and the elongation value of 30.71%.